2021
DOI: 10.3389/fpubh.2021.626697
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Clinical Decision Support System for Early COVID-19 Mortality Prediction

Abstract: The coronavirus disease 2019 (COVID-19), caused by the virus SARS-CoV-2, is an acute respiratory disease that has been classified as a pandemic by the World Health Organization (WHO). The sudden spike in the number of infections and high mortality rates have put immense pressure on the public healthcare systems. Hence, it is crucial to identify the key factors for mortality prediction to optimize patient treatment strategy. Different routine blood test results are widely available compared to other forms of da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 73 publications
(100 reference statements)
3
46
0
Order By: Relevance
“…The top 10 most important variables in the model are presented in Figure 4 and are consistent with those described in several other studies. [23][24][25] The several-fold higher importance values of age and troponin in comparison to other predictors in the model indicate that these two variables were the key predictors of mortality in this cohort. Among the top 10 predictor variables, age, compliance, glucose, INR, body mass index, and CT did not feature prominently as partitioning variables in the LCA model, suggesting that the prognostic value of the LCA classes is independent of common predictors of mortality in COVID-19-related ARDS.…”
Section: Supervised Mortality Predictor Modelmentioning
confidence: 81%
“…The top 10 most important variables in the model are presented in Figure 4 and are consistent with those described in several other studies. [23][24][25] The several-fold higher importance values of age and troponin in comparison to other predictors in the model indicate that these two variables were the key predictors of mortality in this cohort. Among the top 10 predictor variables, age, compliance, glucose, INR, body mass index, and CT did not feature prominently as partitioning variables in the LCA model, suggesting that the prognostic value of the LCA classes is independent of common predictors of mortality in COVID-19-related ARDS.…”
Section: Supervised Mortality Predictor Modelmentioning
confidence: 81%
“…28 Other studies using ML models found elevated neutrophil, CRP, lymphocyte and lactate dehydrogenase levels and advanced age variables as predictors of mortality associated with COVID-19 disease. 29 30…”
Section: Discussionmentioning
confidence: 99%
“…Several machine learning models have been proposed to predict the outcome of COVID-19 patients [27][28][29][30][31]. However, most of the key features of these models are lab values and may not have the ability to provide early COVID-19 mortality prediction.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the performance of these models, most of their AUCs are between 90% and 95%, to which the performance of our model is comparable. Karthikeyan et al [31] proposed a model that performed with AUC of 99% when predicted at the day of outcome but performed worse when it predicted far from the day of outcome. This demonstrated the difficulty of early COVID-19 mortality prediction.…”
Section: Discussionmentioning
confidence: 99%